Advances in Left Ventricular Noncompaction and Its Prevention and Treatment with Traditional Chinese Medicine - Bai, Lirong; Chen, Xuebin (Journal of Contemporary Medical Practice, 2025)
Left Ventricular Noncompaction (LVNC) is a congenital cardiomyopathy characterized by excessively prominent trabeculations and deep intertrabecular recesses within the ventricular cavity. Modern medical management primarily focuses on symptomatic treatment, lacking specific therapeutic agents. In contrast, Traditional Chinese Medicine (TCM), based on the therapeutic principle of “Supplementing Qi and Warming Yang, Activating Blood and Promoting Diuresis, “ demonstrates distinct advantages. It employs multi-component, multi-target interventions to regulate myocardial energy metabolism, suppress inflammatory responses, and ameliorate myocardial fibrosis. The integrated approach of TCM and Western medicine offers a more comprehensive therapeutic strategy for patients with LVNC. Future research should prioritize high-quality clinical studies and in-depth mechanistic exploration.